Incidence of Inadvertent Perioperative Hypothermia in Pediatric Laparoscopic Surgery: a Prospective Observational Single-Center Study - Dagli, Recai; Celtik, Ulgen; Çelik, Fatma; Erbesler, Zeynel Abidin; Mızrak, Zeynep Koylu (My University, 2022)
Purpose: The pediatric age group is a risk group for Inadvertent perioperative hypothermia (IPH) due to insufficient subcutane-ous adipose tissue and underdeveloped thermoregulatory responses. We aimed to determine the frequency of IPH in the pediatric age group undergoing laparoscopic surgery. Materials and Methods: The study is prospective observational. Pediatric patients (1-18 years old) who underwent laparoscopic surgery under general anesthesia were evaluated. The tympanic membrane temperature measurements of the patients (°C) were recorded before anesthesia induction (T0) and then every 15 minutes during the surgery. Results: A total of 100 patients were evaluated. The frequency of inadvertent perioperative hypothermia was detected as 13(13%). The frequency of IPH in elective surgery patients was higher than in emergency surgery (<0.001). IPH occurred in 11 of a total of 28(39.3%) patients during elective surgery. Age, body mass index, intravenous fluid volume, and insufflated CO2 volume of hypothermic patients were detected to be statistically significantly lower than the normothermic group. A significant statistical difference was detected between T0 (°C) of nor-mothermic and hypothermic patients (37.8±0.53 vs. 36.8±0.60, respectively, 95% CI, 37.6 to 37.8, P<0.001). In total, a decrease of approximately 0.7 °C in body temperature was observed in the first 30 minutes. Conclusion: IPH frequently develops during laparoscopic surgeries in the pediatric age group. The current temperature manage-ment practices and passive heating systems that we use do not seem adequate to provide protection from hypothermia.
Keywords: Laparoscopy; Pediatric; General anaesthesia; Accidental hypothermia; Body temperature changes